Rural non-farm employment: Agricultural versus urban linkages - some evidence from Kerala state, India - Mridul Eapen (The Journal of Peasant Studies, Vol.28, No.3, April 2001, pp.67-89, 2001)
Rural non-farm employment is regarded as a critical component of rural transformation in LDCs given the failure of the industrialization-led development strategies of the 1950s. An issue much debated in the restructured development dialogue was: Is the process of rural diversification primarily agriculture-driven, or do the impulses derive from the urban economy? Our study addresses this question for Kerala by examining changes in employment patterns in rural areas between 1971 and 1991. An examination of certain socio-economic characteristics (proxies for 'agricultural' and 'urban' linkages) for 1971 in those villages which became urban in 1991 reveals the importance of both types of linkages in generating non-farm employment, depending on the location of thevillage vis--vis large urban settlements.